2019
DOI: 10.3390/ijerph16132324
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Demographic Characteristics, Lifestyle Health Behaviours, and Quality of Life among Adolescents in Asia Pacific Region

Abstract: Background: Given the risk of physical and psychosocial health that emerge in adolescents that are continuing into adulthood, identifying and addressing early signs of health-related quality of life (HRQoL) decline provides an opportunity to ensure that young people have a healthier progression through adolescence. Aim: To investigate the association between demographic characteristics, lifestyle health behaviours, and HRQoL of adolescents who live in Asia Pacific region, including Hong Kong in China, Beijing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…It seems that older adolescents tended to present a significant increase in the ability to manage their stress after the mHealth intervention (TeenPower). These results confirmed the findings of previous studies that highlight the influence of adolescents' age in the development of stress management skills (Hampel, Meier, & Kümmel, 2008;Lee et al, 2019;Monteiro, Balogun, & Oratile, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…It seems that older adolescents tended to present a significant increase in the ability to manage their stress after the mHealth intervention (TeenPower). These results confirmed the findings of previous studies that highlight the influence of adolescents' age in the development of stress management skills (Hampel, Meier, & Kümmel, 2008;Lee et al, 2019;Monteiro, Balogun, & Oratile, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the significant associations between lifestyle and physical and school functioning became weaker when other stronger variables such as emotion, behavioral control and self-esteem were statistically adjusted in the current study. Earlier, Lee, Chien, Tanida, Takeuchi, Rutja, Kwok and Lee [19] found that the lifestyle domains of physical participation, nutrition and health awareness had weaker associations with the overall quality of life than other domains such as social support and identity awareness. However, perceived social support by age only shows minimal association with social functioning of quality of life when age and other variables were statistically controlled in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…In previous studies, the demographic characteristics such as family-related factors have been shown to be associated with quality of life and psychosocial health conditions among adolescents [16][17][18]. Lee, et al [19] found that adolescent lifestyle and social support were positively associated with quality of life and were different between Asian-Pacific countries. Nowadays, social and cultural changes have created challenges for adolescents to assume roles and responsibilities in health promotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that physical activity (PA) and sedentary behavior (SB) are associated with HRQoL among adolescents ( Jalali-Farahani et al, 2016 ; Wong et al, 2017 ; Lee et al, 2019 ). For instance, after two years of follow-up, Sánchez-Oliva and colleagues found that adolescents who increased their SB had a greater decrease in HRQoL compared to those who changed to active profiles ( Sánchez-Oliva et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%